Pengaruh Latihan Gerak Sendi untuk Menurunkan Nyeri Sendi pada Lansia dengan Osteoartritis - Supriadi, Supriadi; Rahmatin, Susma Aulia; Aupia, Anatun (STIKes Hamzar, 2021)
One of degenerative diseases experienced on the elderly is osteoarthritis, indicated by the existence of pain on under-extremities and its prevalence is increasese alongwith age-rised. Non- pharmacological management is an important component in resolveing a pain, which is Range of Motion Exercise. The Research purpose is to know the effect of lower extremity joint exercise on the level of knee joint pain on the elderly with osteoarthritis at Gubuk Tengak Kelayu Utara. The Research is a quantitative reseach with intervention- study by using Quasi Experiment Design; Pretest-Posttest Control Group. The Research was conducted in Gubuk Tengak Kelayu Utara, East Lombok. The samples of study were 30 elderly, devided to 15 elderly as intervention group and 15 elderly as control group. The Sampling technique was purposive sampling.the variabels of the reaseach were Range of Motion and Pain Scale on elderly. The data Analysis were Wilcoxon Test and Mann Whitney Test. After doing Range of Motion for 2 weeks , it was obtained that there is influence Range of Motion to joints pain scale on elderly with osteoarthritis with p value 0,003 (α <0,05). In conclusion, there is significant effect of Range of motion in decreasing joints’ pain on elderly with osteoarthritis.